The Clinicopathologic Features of 22 Cases With Primary Invasive Papillary Carcinoma of the Breast Identified in 1153 Cases With Invasive Breast Carcinoma: Single-Center Experience - Canan Kelten Talu; Begum Yeni Erdem; Esra Arslan; Mehmet Ali Nazli; Yasemin Cakir; Didem Can Trabulus (European Journal of Breast Health, 2022)

(untitled)
Objective:Invasive papillary carcinoma (IPC) of the breast is an uncommon histologic subtype with limited data in the literature. The aim of this study was to increase the evidence base by presenting clinicopathological findings of cases diagnosed as IPC.Materials and Methods:Hematoxylin and eosin sections and immunostaining of surgical excision specimens diagnosed as invasive breast carcinoma were re-evaluated, retrospectively.Results:IPC was detected in 22 cases (1.9%), of which 7 (0.6%) had pure and 15 (1.3%) had mixed morphology. Histologic types accompanying IPC were: Invasive ductal carcinoma (IDC) (15/15); invasive micropapillary carcinoma (3/15); and pleomorphic lobular carcinoma (1/15). Patient ages ranged between 36 and 89 (median 56.5) and the tumor size from 8 to 70 mm (median 19 mm). The histologic grade was 3 in five cases, 2 in 13, and 1 in four cases. The nuclear grade was 3 in 10 cases and 2 in 12. The values of positivity for estrogen receptor, progesterone receptor, human epidermal growth factor receptor-2, and Ki-67 index indicated Luminal B phenotype in 16 (72.7%), triple-negative in 5 (22.7%), and Luminal A in 1 case (4.6%). Ductal carcinoma in situ was noted in 19 cases (86.4%).Conclusion:IPC was mostly detected as an accompanying carcinoma to IDC at postmenopausal ages and was mostly Luminal B phenotype with intermediate-to-high grade features.